Myogenic Basic Helix-Loop-Helix Proteins and Sp1 Interact as Components of a Multiprotein Transcriptional Complex Required for Activity of the Human Cardiac α-Actin Promoter - Biesiada, Elzbieta (American Society for Microbiology, 1999)
Activation of the human cardiac α-actin (HCA) promoter in skeletal muscle cells requires the integrity of DNA binding sites for the serum response factor (SRF), Sp1, and the myogenic basic helix-loop-helix (bHLH) family. In this study we report that activation of the HCA correlates with formation of a muscle-specific multiprotein complex on the promoter. We provide evidence that proteins eluted from the multiprotein complex specifically react with antibodies directed against myogenin, Sp1, and SRF and that the complex can be assembled in vitro by using the HCA promoter and purified MyoD, E12, SRF, and Sp1. In vitro and in vivo assays revealed a direct association of Sp1 and myogenin-MyoD mediated by the DNA-binding domain of Sp1 and the HLH motif of myogenin. The results obtained in this study indicate that protein-protein interactions and the cooperative DNA binding of transcriptional activators are critical steps in the formation of a transcriptionally productive multiprotein complex on the HCA promoter and suggest that the same mechanisms might be utilized to regulate the transcription of muscle-specific and other genes.